Telling About Islamic Heroes And Female Leaders: Ways Of Implanting Self-Concept, Moral, And Religious Value On Children - Niswatin Nurul Hidayati (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The objectives of national education are realizing the fair and prosper society in term of material and spiritual based on the value of Pancasila, in which the main point is developing Indonesian citizens wholly. One of the most important components of Indonesian citizens is children, because they are the owner of the nation’s future. Thus, it could be said that the implantation of self-concept, moral, and religious values should be started earlier, so that it would be strongly implanted on Indonesian children. One of the methods is storytelling with woman heroes and public figures, whether they are from Indonesia or Islamic history. The consideration in choosing the woman heroes and public figures is as a form of moral education, introducing Islamic religious values, as well as gender education on children. This becomes important because of Indonesian’s social life which is full of various religions, cultures, tribes, race or ethnics, social status and others. The storytelling process as a form of learning media is expected to be applied in kindergarten (TK), Islamic Kindergarten (RA), or elementary school Keywords: storytelling, character education, children, moral education, gender education